Pengaruh Persepsi Social Character AI terhadap Pengungkapan Pribadi (Analisis pada Generasi Z di Indonesia) - Gultom, Sharon Michella; Tobing, Melati Mediana (ARZUSIN, 2026)
Although human interaction with Artificial Intelligence (AI) has received attention in various studies, research that specifically examines the influence of perceived social presence of Character AI on self-disclosure among Generation Z in Jakarta remains limited. This study aims to analyze the influence of perceived social presence of Character AI on self-disclosure among Generation Z in Jakarta. This study used a quantitative approach with an explanatory survey design, involving 96 Generation Z respondents aged 18–29 years who resided in Jakarta and were selected using purposive sampling. Data were collected using a Likert-scale questionnaire to measure perceived social presence of Character AI and the level of self-disclosure, then analyzed through descriptive statistics, validity testing, reliability testing, and simple linear regression with the assistance of SPSS software. The results showed that Generation Z had a high perception of social presence toward Character AI, characterized by feelings of closeness, comfort, and social presence during interactions. The respondents’ level of self-disclosure was also in a relatively high category, particularly in the aspects of opinions, interests, personal experiences, and emotional conditions. The findings showed a positive influence of perceived social presence of Character AI on self-disclosure among Generation Z in Jakarta. The conclusion of this study affirms that perceived social presence plays an important role in encouraging users’ self-disclosure when interacting with AI. Theoretically, this study contributes to the development of digital communication studies and human–AI interaction, while practically it provides implications for AI technology developers in designing systems that are more responsive to users’ emotional needs. This study also opens opportunities for further research on other factors that influence self-disclosure in human–AI interactions.